THE APPLICATION OF CALCIUM AND POTASSIUM FERTILIZER TO DECREASE SODIUM TOXICITY ON PLANT IN COASTAL AREA *) - Karno . (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The research was carried out in April to July 1996 in the coastal area of Semarang in order to evaluate the effect of calcium and potassium fertilizer to plant growth and production of setaria grass and to observe sodium toxicity on the grass. The experiment was arranged in two factor split-plot design with three replication. The main factor was the application of CaCO3 which was divided into three levels : 0, 4 and 8 ton CaCO3/ha and the sub factor was the application of KCl which was divided into three levels: 0, 40 and 80 kg K2o/ha. Eight parameters were observed in this experiment : Total Dissolved Salts (TDS), Soil Electrical Conductivity (ECe), level of death plant, plant height, leaves numbers, fresh yield, dry yield and protein content. The result show that the application of CaCO3 and KCl created inverse effect to Total Dissolve Salts (TDS) and Soil Electrical Conductivity (ECe). On one hand, CaCO3 decrease TDS and ECe and on the other hand. KCl increase TDS and ECe. There were interactions between CaCO3 and Kcl in influencing TDS and ECe. However, CaCO3 and KCl brought about similar effect to plant performance. Both CaCO3 and KCl decreased the level of died plant and increased plant height, leaves number, fresh yield, dry yield an protein content of setaria grass. CaCO3 and KCl did not interact each other in increasing plant performance. The application of CaCO3 increased plant height significantly at week 3, week 4 and week 5, and increased dry yield and protein content significantly, but not increase fresh yield significantly. The application of KCl increased dry yield and protein content significantly, but did not increased plant height, leaves number and fresh significantly. t-fontkiy У so-bidi-font-family: Symbol'>·      property-rights;  user-pays;regulation;education and code of conduct;permanent mooring;socio-economic research. It is also clear that no one management strategy will ensure that Indonesia’s significant  coral reef and other marine are conserved and used in sustainable fashion. Rather, a judicious    blend of the use of economic instruments and concepts, regulation, education, and “site-hardening” (e.g. by use mooring) is required to ensure that marine tourism is sustainable.